A Pedagogical Innovation Framework for Creativity: Developing a Regional-Potential-Oriented Community-Based Learning Model - Amri Dhimas Maulana; Aim Abdulkarim; Enok Maryani; Erlina Wiyanarti; Salman Alparis Sormin; Ahmad Syariful Jamil; Mohamed Saddik (Jurnal Ilmiah Sekolah Dasar, 2026)
Social Studies learning in rural contexts remains largely abstract and disconnected from students’ real-life experiences, limiting their engagement and creativity development. This study aimed to develop a regional-potential-oriented community-based learning (CBL) model for Social Studies education that leverages local coffee potential to enhance students’ creativity in rural contexts. This study employed a Research and Development (R&D) approach based on Borg and Gall, focusing on three main stages: research and information collecting, planning, and developing a preliminary product. The model was validated through expert judgment involving learning model specialists, subject-matter experts, practitioner teachers, and community representatives, followed by a Focus Group Discussion (FGD) to refine the model and its supporting components. Data were analyzed using qualitative descriptive techniques to interpret findings from the preliminary study, expert validation, and FGD, and quantitative descriptive analysis to evaluate the model’s validity and feasibility, as the study had not yet proceeded to the effectiveness testing stage. The findings indicate that the developed learning model is pedagogically coherent, contextually relevant, and practically feasible to implement within the existing Social Studies curriculum. Overall, this study contributes a validated and context-responsive pedagogical model that advances creativity-oriented Social Studies instruction through Community-Based Learning grounded in regional potential.